Pasal 240-241 KUHP Baru Ancaman "KUHP Karet" bagi Kebebasan Berpendapat di Indonesia 2026 - Sangkala, Robert; Komala, ⁠Ida; Wibowo, Satria Ari; Roif, Roif; Asari, ⁠Ali; Candra, Firman Adi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This article analyzes Articles 240-241 of the new Criminal Code (KUHP) proposed in the 2023 KUHP, effective as of January 2, 2026, which impose penalties of up to 4 years imprisonment for insults against the government or state institutions. Using a normative-legal research approach, the article explores the potential for these provisions to be interpreted as a "rubber KUHP" that restricts freedom of expression, as reported to the UN. The analysis compares these articles with Article 19 of the 1945 Constitution, the ICCPR Convention, and UN recommendations, alongside potential case studies such as the criminalization of activists. The findings indicate that these provisions risk undermining civil democracy, despite their intent to protect national dignity. This research emphasizes the urgency of revision to maintain balance between state protection and human rights.